Traditionally used ethnoveterinary phytomedicines and their associated threats in Yeki district, Southwestern Ethiopia - Melese , Daniel; Asnakew , Muluye; Getachew, Samuel; Awoke, Ashebir (Ethnobotany Research and Applications, 2025)
Background: For generations, communities in Yeki district, Southwestern Ethiopia, have relied on ethnoveterinary phytomedicines (EVPMs) as a primary means of treating livestock ailments. However, this traditional knowledge is increasingly at risk due to environmental degradation, cultural shifts, and lack of documentation. This study aimed to document and analyzes the EVPMs and associated indigenous knowledge used in local livestock healthcare. Methods: A total of 170 informants were selected through purposive and snowball sampling. Quantitative ethnobotanical tools such as Informant Consensus Factor (ICF), Fidelity Level (FL), Preference Ranking (PR), Pairwise Comparison (PWC), and Direct Matrix Ranking (DMR) were applied. Statistical tests (t-test, ANOVA, correlation, regression) were conducted using R to evaluate knowledge variation among informants. Results: Fifty medicinal plants from 34 families were recorded for treating 21 livestock ailments, including wounds, trypanosomiasis, rabies, bloating, and diarrhea. Asteraceae, Euphorbiaceae, and Solanaceae were the most cited families. Herbs were dominant, with leaves and roots the most used parts, mainly administered orally. The highest ICF (0.94) was for external parasites, and J. schimperiana had the highest FL (94%) for treating intestinal parasites. Agricultural expansion and grazing were major threats. Knowledge of EVPMs significantly varied among informant groups (P < 0.05). Conclusion: The community holds rich ethnoveterinary knowledge with diverse EVPMs, many of which are under threat and lack conservation. Collaborative efforts with institutions like Mizan Tepi University are vital for conservation and scientific validation of these medicinal plants. Keywords: Ethnoveterinary, Phytomedicines, Threats, Yeki district, Ethiopia.